2020
DOI: 10.1002/ange.202011521
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Planarity in the Design of Organic Electronic Materials

Abstract: Planarity is essential for many organic electronic materials as it maximizes the intramolecular p-orbital overlap and enables efficient intermolecular interactions through pstacking. We propose as tatistical way of quantifying the planarity of awide range of conjugated systems.The quantification takes into account all torsional conformations and their relative contribution to the overall structural disorder,through ap lanarity index hcos 2 fi.T he propensity for planarization and the effect of rotational disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…We envisaged that an increase of the interplanar angle (φ DA ) between the anion and the cation moieties of 1a derivatives would decrease E Int . We then designed the π-conjugated zwitterions 2a – 4a by the benzoannulation to 1a because φ DA would be increased by the steric hindrance (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…We envisaged that an increase of the interplanar angle (φ DA ) between the anion and the cation moieties of 1a derivatives would decrease E Int . We then designed the π-conjugated zwitterions 2a – 4a by the benzoannulation to 1a because φ DA would be increased by the steric hindrance (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, we performed DFT calculations to estimate the planarity of the polymer building block combinations by using a recently developed planarity indexes ⟨cos 2 φ⟩ 30 . We found that TDPP can form planar polymer backbone with TQ and BBT with high torsional barriers and large ⟨cos 2 φ⟩ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This new type of electron acceptor differs from the traditional INCN-type acceptors that possess flexible σ bonds, and shows an all-fused-ring molecular framework, 59 resulting in a considerably reduced reorganization energy compared with IDIC, 60 a classical small-molecule electron acceptor, 0.16 versus 0.20 eV based on density functional theory (DFT) calculations at the B3LYP/6-31G** level. Compared with IFDM, ITYM exhibits significantly elevated highest occupied molecular orbital (HOMO) (−5.77 vs −6.49 eV) and LUMO energy levels (−3.59 vs −3.95 eV) that are suitable for the OPV application.…”
Section: Introductionmentioning
confidence: 95%